Impact of Universal Health Coverage on Child Growth and Nutrition in Argentina - Nuñez, Pablo Alfredo (2016)
Objectives. To estimate trends of undernutrition (stunting and underweight) among children younger than 5 years covered by the universal health coverage programs Plan Nacer and Programa Sumar. Methods. From 2005 to 2013, Plan Nacer and Programa Sumar collected high-quality information on birth and visit dates, age (in days), gender, weight (in kg), and height (in cm) for 1.4 million children in 6386 health centers (13 million records) with broad coverage of vulnerable populations in Argentina. Results. The prevalence of stunting and underweight decreased 45.0% (from 20.6% to 11.3%) and 38.0% (from 4.0% to 2.5%), respectively, with differences between rural versus urban areas, gender, regions, age, and seasons. Conclusions. Undernutrition prevalence substantially decreased in 2 programs in Argentina as a result of universal health coverage.